2018
DOI: 10.1103/physrevb.97.041112
|View full text |Cite
|
Sign up to set email alerts
|

Soft antiphase tilt of oxygen octahedra in the hybrid improper multiferroicCa3Mn1.9Ti0.1O7

Abstract: We report a single crystal neutron and x-ray diffraction study of the hybrid improper multiferroic Ca3Mn1.9Ti0.1O7 (CMTO), a prototypical system where the electric polarization arises from the condensation of two lattice distortion modes. With increasing temperature (T ), the out-of-plane, antiphase tilt of MnO6 decreases in amplitude while the in-plane, inphase rotation remains robust and experiences abrupt changes across the first-order structural transition. Application of hydrostatic pressure (P ) to CMTO … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…9) is quite clear, as is the relative lack of change in octahedral twist about the c axis (X þ 2 ). Our results are in good agreement with those of more sophisticated studies such as that of Ye et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…9) is quite clear, as is the relative lack of change in octahedral twist about the c axis (X þ 2 ). Our results are in good agreement with those of more sophisticated studies such as that of Ye et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…In Figure 2D, the pronounced phase coexistence phenomenon can be observed at 373 K, where the contents of A2 1 am and Acaa phases are 39.9(5) wt% and 60.1(7) wt%, respectively. The single-crystal diffraction measurement indicated that a polar Aba2 phase exists at 450 K. 34 However, the Rietveld refinement results performed at 473 K show that the nonpolar Acaa structure provides a much better goodness-of-fit χ 2 than that of polar Aba2 phase, demonstrating the presence of Acaa phase (see Figure 1 and Table 2). Figure 2E shows that the lattice parameters increase until the discontinuities appear above 373 K. Then the parameters a, b, and cell volume indicate a sharp increase, while the parameter c starts to decrease with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, however, it remains challenging to observe the switchable polarization at room temperature, and its inferior remanent polarization (~1 μC/cm 2 for polycrystalline and ~6.4 μC/cm 2 for single-crystal Ca 3 Ti 2 O 7 ) also limits the investigation and application. 9,34,39,40 Therefore, systematic studies of Ca 3 [Mn 1x (Fe 0.5 Nb 0.5 ) x ] 2 O 7 (x = 0.15, 0.25, and 0.50) ceramics have been conducted to tune the crystallographic symmetry and ferroelectricity. The microstructures and distribution of grain size of dense Ca 3 [Mn 1x (Fe 0.5 Nb 0.5 ) x ] 2 O 7 ceramics are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Several theoretical and experimental efforts are still devoted to understand HIF in perovskites and related materials and to rationalize rules maximizing the polarization 57,101,[152][153][154][155][156]126,128,141,142,146,[149][150][151] . One key point is to understand the phase transition of these materials:…”
Section: Figure 8: Illustration Of Anti-polar Displacements In Bulk Abo3 Compounds (A) and Ferri-like Polar Distortions In (Abo3)1/(a'bo3mentioning
confidence: 99%